Quantum Physics Meets the Philosophy of Mind : New Essays on the Mind-Body Relation in Quantum-Theoretical Perspective - Corradini, Antonella; Meixner, Uwe (Philosophische Analyse, 2014)
"Quantum physics, unlike classical physics, suggests a non-physicalistic metaphysics. Whereas physicalism implies a reductive position in the philosophy of mind, quantum physics is compatible with non-reductionism, and actually seems to support it. The essays in this book explore, from various points of view, the possibilities of basing a non-reductive philosophy of mind on quantum physics"--Provided by publisher